Understanding Patient Adherence to Hypertension Management Guidelines - Qiu, Haixin; Piskorz-Ryń, Oriana (KMAN Counseling & Psychology Nexus, 2024)
Hypertension is a prevalent chronic condition globally, associated with an increased risk of cardiovascular diseases. Effective management of hypertension is crucial to prevent these complications; however, adherence to management guidelines is often suboptimal. This study aimed to explore the factors influencing patient adherence to hypertension management guidelines to identify areas for intervention and improvement. This qualitative study utilized semi-structured interviews to collect data from 30 participants diagnosed with hypertension. Participants were selected using purposive sampling to ensure a diverse representation in terms of age, gender, and ethnicity. The interviews were designed to explore various aspects of hypertension management as experienced by the patients. Data analysis was conducted using NVivo software, employing thematic analysis to identify and categorize themes related to adherence. Four main themes were identified as significant influencers of adherence to hypertension management guidelines: Patient Understanding, Health System Factors, Lifestyle and Management, and Personal and Social Influences. Each theme comprised several categories with specific concepts: Knowledge of Hypertension, Accessibility of Healthcare, Diet and Nutrition, and Cultural Beliefs, among others. These themes highlighted the complexity of factors affecting patient adherence, ranging from individual knowledge and behaviors to systemic and social influences. The study underscores the multifaceted nature of factors influencing adherence to hypertension management guidelines. Enhancing adherence requires a holistic approach that addresses not only medical and educational aspects but also considers systemic improvements and personalized patient support. Interventions should focus on improving patient education, healthcare accessibility, and support systems while acknowledging the role of personal and cultural factors in health management.